Modern directions in library services with use of digital space (Security issues of the regional and industry information service) - Kazimi, Parviz Firudın oqlu; Mahammadli, Dashgin Heydar oglu (Technium Social Sciences Journal, 2021)
Modern libraries are active participants in global information processes. They work in a wide range of fields, from the application of the latest technology to the development of new information products and the introduction of new assessment technologies. However, the process of “dictating the terms” takes place on platforms in which the libraries do not participate. The commercialization of information services also excludes libraries. In this confrontation, libraries, as institutions influencing the information environment, stand next to the state and try not to lose their attractiveness. In this respect, libraries can act as a bridge between local and regional as well as global networks. Libraries, academic and university libraries currently operating in the world and responding to modern challenges are the main participants in the authoritative information cycle. Coordination of the information activities of these agencies can lead to significant improvements in the information environment. The main goal of the study is to determine the optimal forms and methods of using the possibilities of digital space in libraries. The article also outlines his views on how to ensure the effectiveness and coverage of information services.